Overexpression of JAK2: a predictor of unfavorable prognosis for nasopharyngeal carcinoma. (August 2016) - He, Hong-Lin; Lee, Ying-En; Liang, Peir-In; Lee, Sung-Wei; Chen, Tzu-Ju; Chan, Ti-Chun; Hsing, Chung-Hsi; Chang, I-Wei; Shiue, Yow-Ling; Li, Chien-Feng
Purpose: Analysis of the nasopharyngeal carcinoma public transcriptome revealed JAK2 was significantly upregulated in tumors, which encouraged us to investigate its prognostic significance and mutational status.Materials & methods: We assessed the immune-expression of JAK2 and its relationships with various clinicopathological parameters. JAK2 mutation was detected by PCR followed by sequencing.Results: High expression of JAK2 was significantly associated with advanced tumor staging (p = 0.019). JAK2 overexpression acted as an independent predictor for worse disease-specific survival (p = 0.005), distant metastasis-free survival (p = 0.036), local recurrence-free survival (p = 0.012) and overall survival (p = 0.007). JAK2 mutation was not detected in selected cases with JAK2 protein overexpression.Conclusion: JAK2 can serve as a valuable negative prognostic factor and a potential therapeutic target.